Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1471-4159.2010.07167.x
|View full text |Cite
|
Sign up to set email alerts
|

SynArfGEF is a guanine nucleotide exchange factor for Arf6 and localizes preferentially at post‐synaptic specializations of inhibitory synapses

Abstract: Chemical synapses are specialized sites of the communication between neurons where information is processed and integrated. Electron microscopy has allowed morphological Received November 24, 2010; revised manuscript received December 8, 2010; accepted December 9, 2010. Address correspondence and reprint requests to Hiroyuki Sakagami, MD, PhD, Department of Anatomy, Kitasato University School of Medicine, Sagamihara, Kanagawa 252-0374, Japan. E-mail: sakagami@med.kitasato-u.ac.jp Abbreviations used: Arf, AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 69 publications
2
60
0
Order By: Relevance
“…30 Interestingly, both BRAG1 and BRAG2 are abundant in the PSDs of excitatory synapses, while BRAG3 localizes exclusively to inhibitory GABAergic synapses. 31,32 Consistent with their localization, both BRAG1 and BRAG2 bind the excitatory synapse scaffolding protein PSD95 via their C-terminal PDZ motifs 33,34 while BRAG3 interacts with the inhibitory synapse scaffold gephyrin. 35 Mutations in BRAG1 have been discovered in families with non-syndromic X-linked intellectual disability (XLID).…”
Section: Brags In the Brainmentioning
confidence: 81%
“…30 Interestingly, both BRAG1 and BRAG2 are abundant in the PSDs of excitatory synapses, while BRAG3 localizes exclusively to inhibitory GABAergic synapses. 31,32 Consistent with their localization, both BRAG1 and BRAG2 bind the excitatory synapse scaffolding protein PSD95 via their C-terminal PDZ motifs 33,34 while BRAG3 interacts with the inhibitory synapse scaffold gephyrin. 35 Mutations in BRAG1 have been discovered in families with non-syndromic X-linked intellectual disability (XLID).…”
Section: Brags In the Brainmentioning
confidence: 81%
“…Recently S-SCAM was shown to bind also SynArfGEF, which selectively activates Arf6, a GTP-binding protein member of the ADP ribosylation factor family. S-SCAM is able to interact also with several MAGUKs (including PSD-95, SAP97 and Homer) [103]. Further, these authors showed that SynArfGEF also interacts with dystrophin and utrophin via its PDZ domain and that it colocalizes with dystrophin and gephyrin at GABAergic synapses.…”
Section: The Dystrophin-glycoprotein Complexmentioning
confidence: 91%
“…Interaction between α-dystroglycan and α-/β-neurexins by means of laminin-neurexin-sex hormone-binding globulin (LNS)/laminin G domains has been reported several years ago [101], and was proposed to compete with α-latrotoxin binding on neurexins. In addition, binding of synaptic scaffolding molecule (S-SCAM) to β-dystroglycan and NL2 has been characterized in studies showing the selective presence of S-SCAM at inhibitory synaptic sites [102,103]. S-SCAM has been identified for its synaptogenic role and interactions with NMDA-receptor subunits and NLs.…”
Section: The Dystrophin-glycoprotein Complexmentioning
confidence: 99%
“…Of these, BRAG1, BRAG2, and BRAG3 (brefeldin-resistant Arf GEFs) comprise a subfamily that is characterized by the presence of an IQ motif N-terminal to the catalytic domain. Although BRAG1 (6) and BRAG3 (7) are predominantly expressed in the brain, BRAG2 appears to be ubiquitously expressed (8).…”
mentioning
confidence: 97%